Cultural intervention based on "Bhuppa Bhabhu Ghuru Rato" to overcome early marriage in Torjun Sampang - Safira Anisa Dewi; Maulia Gitawati Indiswari; Rhein Sasi Kirana; Siska Novita Gozaly; Herdina Indrijati (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Pondok Pesantren Darussalam Torjun is addressing the high incidence of early marriages, which significantly impact students' education. Data shows that 41 percent of women in Torjun Village marry before 21, leading to issues like low educational attainment, health risks, and economic challenges. To combat this, a cultural intervention program, BHUPPA-BHABHU-GHURU-RATO, was developed in collaboration with partners. The program aims to increase students' knowledge about early marriage and assertive communication, raise parental awareness of early marriage impacts, and provide a curriculum and educational media on the subject. The initiative targets 77 students, 20 parents, 5 school administrators, health center staff, religious affairs office staff, and the sub-district head. The methods include psychoeducation and the dissemination of curriculum and educational media. The program comprises two parts: community empowerment, involving activities for students, parents, school administrators, and government officials, and cadre development, focusing on peer counseling and persuasive communication training. Results showed a 16 percent increase in students' understanding of early marriage dangers, a 3 percent increase in assertive communication knowledge, and a 10 percent increase in parental awareness. The program's sustainability is supported by curriculum integration, the use of educational media, and the Anti-Early Marriage Knights system.